Gestão democrática na escola de ensino integral: limites e possibilidades - Quaresma, Daniel Gelini (2015)
This research investigates the limits and possibilities of the realization of democratic management in a state full-time school in São Paulo, considering the principles of dialogue, participation and autonomy proposed by Paulo Freire in his liberating pedagogy. Focused on school management, this study describes the setting up of conditions for the reorientation of actions within full-time schooling in order to reorganize them and reinvent them, aiming to address the needs of students. As school management does not manifest itself in a neutral manner conditioned to a type of education and outcomes subject to a number of conceptions and interests within the school realm it is expected, through democratic action, that every player involved in the school community internalizes the cultural identification and valorization towards effective participation in the social gathering. Results point to feasible democratic management possibilities in Full-time Schooling Programs, driven by the creation of new conditions for the tackling of challenges and limitations spawned by the need to execute a shared, participative and non-alienated managerial action